Too much at stake to uphold sport integrity?: high-performance athletes’ involvement in match-fixing - Tak, Minhyeok (Crime, law and social change, 2020)
Non-betting-related match-fixing constitutes an important integrity issue in contemporary sports. With varied forms ranging from passive tanking to the purposeful, coercive, calculated bribing of others to gain advantages, non-betting-related match-fixing can be a form of corruption that deters sport development. This paper examines high-performance athletes’ involvement in non-betting-related match-fixing in South Korea. Drawing from survey data (n = 731), this paper describes and analyses the prevalence of match-fixing, its locales (i.e., levels of competition) and origins (i.e., who made the offer/approach). Results show that: (1) 74 athletes (10.12%) were approached to take part in match-fixing, while 33 of those athletes (4.51%) actually participated; and (2) the match-fixing offers were usually made ‘by coaches’, ‘at high school-level nationwide competitions’, ‘for the purpose of entering universities’. Finally, this paper concludes by suggesting that the excessive incentives (e.g., university admission) linked with elite sport development structures may account for the strong motive behind non-betting-related match-fixing, and its endangering of sport integrity.